Cross-border cosmopolitans : the making of a Pan-African North America - Adjetey, Wendell Nii Laryea (The University of North Carolina Press, 2023)
"Twentieth-century African American history cannot be told without accounting for the significant influence of Pan-African thought, just as the story of U.S. policy from 1900 to 2000 cannot be told without accounting for fears of an African World. [...] By contending that twentieth-century global Black liberation movements began within the U.S.-Canadian borderlands as cross-border, continental struggles, Cross-Border Cosmopolitans reveals the revolutionary legacies of the Underground Railroad and America's Great Migration and the hemispheric and transatlantic dimensions of this history"--